The cultural landscape of the Linares-La Carolina mining district (Spain) - Peréz Sánchez, Antonio Angel; Lorenc, Marek W. (Geotourism/Geoturystyka, 2018)
The Linares-La Carolina mining district is located in the north of Andalusia. In 1999, the European partners of the MINET (European Mining Heritage Network) Project visited the district and described it as “The best kept secret in Europe”. This is a heritage of international historical, technological, cultural and economic importance with an exceptional concentration of remains. Some of these, unmatched anywhere, represent 4000 years of mining history, and of an intense “Industrial Revolution” that shaped a unique cultural landscape. The great importance of the mining and smelting activities in the area during the industrial period resulted in numerous different buildings that changed the aspect of the place and left their mark in towns and villages, creating a distinctive landscape. The ore dressing floors, significant features in themselves, gave rise to huge waste accumulations, tailings and dams that deeply mark the landscape. The first Cornish pumping engine was installed in Pozo Ancho Mine in 1849, proving to be such a success that a great proportion of the area’s mines were equipped with these Leviathans of the industrial world. There are still a great number of Cornish pumping Engine Houses in the district. Their robust construction has allowed them to continue to stand out as reference points in the landscape and as symbols of industrial architecture. The Linares-La Carolina District has probably one of the largest concentrations of pumping engine houses in the world. Six important foundries (La Cruz, Arroyo Hidalgo, La Esperanza, La Tortilla, La Fortuna and San Luis) were working at the same time in Linares, and three more in La Carolina. In these, galena was smelted to produce metallic lead. The ancient mining routes, and the revaluation of an Iberian-Roman settlement, are foci for several archaeological investigations currently being carried out in the area. These have confirmed the antiquity of the mining and smelting. These could be included as part of the tourist experience. A reconstruction of the Iberian-Roman settlement, including a small village and a mine, could be a key element illustrating how this area developed at the start of its mining history. Currently, several projects are turning the mining heritage into a real resource for social regeneration and as an attraction for visitors. The landscape of the Linares-La Carolina mining district should be a real museum that people would wish to visit. There is a need to preserve and interpret both artifacts and a way of life. The Arrayanes Project has been, and must be in the future, a partnership between the local people and their heritage. A long term aim is to get the Mining Landscape of the the Linares-La Carolina district designated as a UNESCO World Heritage Site. // Rejon górniczy Linares-La Carolina leży w północnej Andaluzji. W 1999 r. partnerzy europejskiego projektu MINET (European Mining Heritage Network), stanowiącego zalążek późniejszej Europejskiej Sieci Dziedzictwa Górniczego ‘EUROPAMINES’, odwiedzili ten rejon i określili go jako „Najlepiej trzymaną tajemnicę w Europie”. Jest to dziedzictwo o międzynarodowym znaczeniu historycznym, technologicznym, kulturowym i ekonomicznym, będące szczególnym nagromadzeniem tego typu zabytków. Niektóre z nich, niespotykane nigdzie indziej, przedstawiają 4000 lat historii górnictwa i nasilonej „Rewolucji Przemysłowej”, która ukształtowała unikalny krajobraz kulturowy tej części Hiszpanii. Wielkie znaczenie działalności górniczej i hutniczej na tym obszarze, w okresie przemysłowym skutkowało powstaniem wielu rozmaitych budowli, które zmieniły aspekt tego miejsca i pozostawiły swoje znamię w miastach i wsiach, tworząc charakterystyczny krajobraz. Zakłady przetwórcze rudy, bardzo charakterystyczne same w sobie, dały początek gromadzeniu się wielkiej ilości odpadów, hałd dobitnie znaczących tutejszy krajobraz. Pierwszy parowy silnik maszyny odwadniającej, pochodzący z Kornwalii, został z sukcesem zainstalowany w szybie Pozo Ancho w 1849 r. Niebawem znaczna część kopalni na tym terenie została wyposażona w podobnego typu „olbrzymy” świata przemysłowego. Do chwili obecnej na tym obszarze istnieje wiele maszynowni typu kornwalijskiego, zarówno pompowych jak i wyciągowych. Ich mocna konstrukcja pozwoliła przetrwać jako punkty odniesienia w krajobrazie i jako symbole architektury przemysłowej. Rejon Linares-La Carolina reprezentuje przypuszczalnie największe zagęszczenie maszynowni tego rodzaju na świecie. Równocześnie funkcjonowało w Linares sześć hut (La Cruz, Arroyo Hidalgo, La Esperanza, La Tortilla, La Fortuna i San Luis) oraz dwie w La Carolina. W nich z galeny wytapiano metaliczny ołów. Dawne szlaki górnicze oraz pozostałości osadnictwa iberorzymskiego są miejscami aktualnie prowadzonych wnikliwych badań archeologicznych. Właśnie one potwierdziły wiekowość tutejszego górnictwa i hutnictwa. Stanowiska archeologiczne zostaną włączone do kompleksowej oferty turystycznej. Rekonstrukcja dawnego osadnictwa, z drobnymi wioskami i kopalniami włącznie, może być ważnym elementem ukazującym, jak obszar ten rozwijał się u początków swojej górniczej historii. Obecnie, wiele projektów badawczych przywraca dziedzictwo górnicze do właściwych zasobów wartości społecznej i jako atrakcję dla odwiedzających. Cały rozległy obszar górniczy Linares-La Carolina powinien stać się otwartym muzeum, które społeczeństwo chciałoby odwiedzać. Długoterminowym projektem jest rozpoczęcie procedury zgłoszenia Krajobrazu Górniczego rejonu Linares-La Carolina na listę Stanowisk Światowego Dziedzictwa UNESCO.